Verbal Harassment of Children in the Real and Virtual World: Evidence from Serbia - Bošković, Milica; Stevanović, Nemanja; Suknović, Mina (Sociološki pregled, 2025)
Children belong to one of the vulnerable social groups and, because of their age and intellectual, psychological, and emotional characteristics, they easily become victims of various deceptions or harassment. The aim of the research presented in this article was to examine how many children in Serbia were exposed to verbal harassment in the real and/or virtual world, and what health consequences the victims experienced, as well as whether they reported the harassment and to whom. Two main indicators were the victims’ sex and age. The primary goal was to determine how widespread verbal violence against children was and whether it was more prevalent in the real or virtual world. We examined a total of 980 primary and secondary school students who participated in the research – 511 (52.2%) girls and 469 (47.8%) boys – through anonymous questionnaires. The research was conducted in five cities in Serbia: Belgrade (the capital) and four cities from different geographical regions. It was carried out from February 2023 to April 2023. We analyzed the answers by the sex and age of the respondents, and the results were also assessed based on these two demographic characteristics. The data suggested that 64.6% respondents were victims of verbal harassment in both the virtual and real world. The research showed that more than 40% girls and more than 20% boys were victims of some form of verbal harassment.
Keywords: bullying; harassment; children; Serbia; consequences